Perekayasaan Mixer Settler untuk Ekstraksi Siklus II pada Recovery Uranium dalam Larutan Asam Fosfat - Jami, Abdul; Nuri, Hafni Lissa (BRIN Publishing, 2013)
Mixer settler is technically designed for extraction and separation process of uranium from phosphoric acid solution. Design calculation results shows that: the mixer settler consists of two parts: part of extraction process in the mixer tank and part of separation process in settler tank. The mixer tank type of box with 4 baffles, the size of mixer tank, 0.8 m width, 0.8 m length, 1 m high of liquid, 1.05 m high of mixer tank, stirrer type of disk 6 blade, and power of mixing 4 hp and the settler tank type of rectangular with size of settler tank, 0.8 m width 5 m length, 1 m high of liquid, 1.05 m high of settler tank. For uranium recovery efficiency up to 91%, extraction process is done in 3 stage counter current flow using a solvent Organic (O) DEHPA-TOPO in Kerosene at a phase of ratio A/O of 2:1. The aqueous enter through stage 3 and the organic solvent enter through stage 1. The process of settling occurred with the value of settling velocity is 0.000694 m/s, dispersion factor Ψ = 0.3638 and the light fraction as the dispersed phase and value of Reynolds number (NRE) = 3,438. Because of the Reynolds number is lower than 5,000, it indicates that the quality of the separation is very good.